Employing automotive security to improve the security of unmanned aerial vehicles - Han, Kyusuk (Frontiers in Communications and Networks, 2023)
The concern about cyber threats on unmanned aerial vehicles (UAVs) increases as they become more sophisticated and widely used in various areas. Although there have been efforts to improve the security of UAVs, their focus is limited to physical attacks and securing communication, and many areas remain open to issues. Although a more comprehensive approach is required to improve the overall areas of UAVs, it is reasonable to investigate the case study from the perspective of other similar cyber-physical systems (CPSs). Thus, we see the architectural similarity between UAVs and automobiles. Automotive security has seen significant improvement throughout the last decade as vehicles have begun to have connectivity and autonomy. There have been extensive research and development efforts in various aspects, including securing the components, securing communications, securing software updates, and securing the overall management system to provide multi-layered security for the automotive environments, and standardization and regulations are being issued. Due to the similarity, the employment of ideas from the automotive environments in the UAV environments becomes a reasonable approach. In this paper, we show the automotive security trends and discuss how UAV environments are comparable to automotive environments. We then show how security in automotives is adapted in UAVs with a case study.